Effects of cassava (Manihot esculenta Crantz) density under rice-cassava intercropping in the west of Côte d’Ivoire - Urbain, Konan Kouassi; Frank, Bahan M.L.; Koné, Brahima; Florent, Zadi; Alphonse, Bouet; Jules, Keli Z.; Albert, Yao-Kouamé (Annals of Tropical Research, 2023)
In western Côte d’Ivoire, the rice-based cropping system is characterized by cassava intercropping where the rice yield decreases with high densities of cassava. Hence, the need to determine the optimum densities of the associated crops. A trial was set up on plateau soil (Ferralsol) at the main research station of National Center of Agronomic Research in Man city (western Côte d’Ivoire). Five cropping systems were compared in a Fisher experimental design: single rice cropping, single cassava cropping, and three densities of cassava associated with rice (20cm×20cm). The main observations were focused on respective agronomic data of rice and cassava, including yields, land equivalent ratios and area-time equivalent ratios. The results showed rice grain yield decreasing from 1.78–0.81t ha-1 with the increasing density of cassava yielding between 22.39–34.68t ha-1. The optimum density of cassava was 3333 plants/ha (3m×1m) for yield and LER (>1) coefficient while the ATER ratio was always low (<1) and the difference between cropping cycles was observed. Exploring new calculation methods of the ATER for cassava-rice association was recommended as a future research topic.